ANALISIS SPESIFIKASI TEKNIS SISTEM PENGEMUDIAN ELEKTRIK PADA KENDARAAN LISTRIK BERBASIS BATERAI KOMERSIAL POPULER - Syamaidzar, Ahmad Luqyanto; Putra Padang, Christian Felix; Satya Kumara, I Nyoman; I Gusti Agung Putu, Raka Agung (Jurnal SPEKTRUM; Vol 11 No 1 (2024): Jurnal SPEKTRUM, 2024)
The increase in the number of motor vehicles in Indonesia has elevated the negative impact on the environment, both in terms of air pollution and global warming. According to the Ministry of Transportation (Kemhub), the number of motor vehicles in Indonesia reached 141.99 million units in 2021. The electrification of motor vehicles is one of the solutions to reduce emissions from the motor vehicle sector. This is supported by Presidential Regulation No. 55/2019 to stimulate the growth of the national battery-based electric vehicle (BEV) industry. This paper reviews battery-based electric vehicle (BEV) technology worldwide, especially four-wheeled vehicles with a high total population. The research was conducted through online surveys in 2023 using international data sources and the Association of Indonesian Automotive Industries (GAIKINDO), resulting in a database of 33 battery-based electric vehicles. From this database, it was found that the majority of electric cars purchased by the public are hatchback and sport utility vehicle (SUV) types. In terms of electric drive systems, the power capacity range of electric motors used by these vehicles is between 20 - 150 kW for hatchbacks and 100 - 406 kW for SUVs. The most commonly used electric motor type, constituting about 64%, is the Permanent Magnet Synchronous Motor (PMSM). About 70% of these vehicles use lithium-ion battery technology. The technical specifications of these popular electric cars are expected to assist stakeholders in quickly understanding the technical specifications of electric drive systems in battery-based electric vehicles, serving as a benchmark for designing electric cars suitable to meet domestic needs.